IMPLEMENTATION OF BANK BCA'S RISK MANAGEMENT STRATEGY IN FRANCHISE-BASED BUSINESS FINANCING - Dhea Junita; Marsha Eldrida; Iga Febrina; Adelia Novriani; Hendrawan; Abisatya Bora; Rahma Maulita Sari (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2023)
How to Implement Bank BCA's Risk Management Strategy in Franchise-Based Business Financing, How is the Impact of Bank BCA's Risk Management Strategy Implementation on Franchise-Based Business Financing Literature research methods are used because sources come from journals, research reports, the internet, and other sources. This research approach uses descriptive qualitative techniques. Aiming to provide an overview of the implementation of Bank BCA's risk management strategy in franchise-based corporate financing, the results of this study show the discussion of financing strategies and their impact on franchise businesses. Capital loan financing, especially in franchises to develop business, PT Bank BCA must carry out a comprehensive loan collection process and this is done to avoid the risk of bad loans, especially in the case of large loans. In addition, the bank must also assess the business continuity of the debtor and require management and supervision to maintain the continuity of the bank's business. The impact of this risk occurs when the debtor does not fulfill the contents of the credit agreement, chooses the right prospective debtor in the process of providing credit, and when the bank's HR is deceived by the appearance of the prospective debtor. Therefore, it is important to apply the 5 C's principle.